Synergistic Effect of Berberine Hydrochloride and Fluconazole Against Candida albicans Resistant Isolates - Yong, Jiangyan; Zu, Ruiling; Huang, Xiaoxue; Ge, Yiman; Li, Yan (Frontiers in Microbiology, 2020)
The emergence of resistant Candida albicans has made clinical fluconazole (FLC) treatment difficult. Improving sensitivity to FLC is an effective way to treat resistant isolates. Berberine hydrochloride (BBH) is a commonly-used traditional Chinese medicine with antimicrobial effects, especially in resistant isolates. We investigated the molecular mechanisms underlying BBH and FLC synergism on biofilm-positive FLC-resistant C. albicans inhibition. Checkerboard microdilution assays and time-kill assays showed a strong synergistic effect between BBH and FLC in resistant C. albicans isolates, causing a significant 32–512-fold reduction in minimum inhibitory concentrations. BBH combined with FLC inhibited intracellular FLC efflux due to key efflux pump gene CDR1 downregulation, whereas FLC alone induced high CDR1 transcription in resistant strains. Further, BBH + FLC inhibited yeast adhesion, morphological hyphae transformation, and biofilm formation by downregulating the hyphal-specific genes ALS3, HWP1, and ECE1. BBH caused cytoplasmic Ca2+ influx, while FLC alone did not induce high intracellular Ca2+ levels. The vacuolar calcium channel gene YVC1 was upregulated, while the vacuolar calcium pump gene PMC1 was downregulated in the BBH + FLC and BBH alone groups. However, vacuolar calcium gene expression after FLC treatment was opposite in biofilm-positive FLC-resistant C. albicans, which might explain why BBH induces Ca2+ influx. These results demonstrate that BBH + FLC exerts synergistic effects to increase FLC sensitivity by regulating multiple targets in FLC-resistant C. albicans. These findings further show that traditional Chinese medicines have multi-target antimicrobial effects that may inhibit drug-resistant strains. This study also found that the vacuolar calcium regulation genes YVC1 and PMC1 are key BBH + FLC targets which increase cytoplasmic Ca2+ in resistant isolates, which might be critical for reversing biofilm-positive FLC-resistant C. albicans.